2008
DOI: 10.1021/nl072369t
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observation of an Extremely Dark Material Made By a Low-Density Nanotube Array

Abstract: An ideal black material absorbs light perfectly at all angles and over all wavelengths. Here, we show that low-density vertically aligned carbon nanotube arrays can be engineered to have an extremely low index of refraction, as predicted recently by theory [Garcia-Vidal, F. J.; Pitarke, J. M.; Pendry, J. B. Phys. Rev. Lett. 1997, 78, 4289-4292] and, combined with the nanoscale surface roughness of the arrays, can produce a near-perfect optical absorption material. An ultralow diffused reflectance of 1 x 10(-7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
520
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 634 publications
(551 citation statements)
references
References 21 publications
18
520
3
3
Order By: Relevance
“…6 Nanowires exhibit novel properties of interest for applications in light emission, 1 biosensing, 7 and next-generation solar cells. [2][3][4][5] Light scattering is inherent to many nanostructured materials and holds promise for new approaches to light management in thinfilm devices.…”
mentioning
confidence: 99%
“…6 Nanowires exhibit novel properties of interest for applications in light emission, 1 biosensing, 7 and next-generation solar cells. [2][3][4][5] Light scattering is inherent to many nanostructured materials and holds promise for new approaches to light management in thinfilm devices.…”
mentioning
confidence: 99%
“…For example, Yang et al 1 report that nanotube forests are among the blackest known materials when observed along the axes of the nanotubes. However, at other angles of incidence, nanotube forests are noticeably reflective, particularly from their sidewalls.…”
mentioning
confidence: 99%
“…But he says that making a perfect black in the visible range will be hard, because the components would have to be so small. A super-black material made from carbon nanotubes was reported recently 4 , in which the high absorbance comes from the roughness of the surface rather than the antenna action of metamaterials.…”
Section: Sidelinesmentioning
confidence: 99%